DEVELOPMENT OF STUDENTS' SELF-EDUCATION MOTIVATION THROUGH THE UNIVERSITY SCIENTIFIC LIBRARY - Mustofaqulova, Maftuna (Журнал иностранных языков и лингвистики, 2023)
It is known that libraries have been a center of spirituality and enlightenment for people since ancient times, and the human race has always lived in search of books. Libraries have always been an integral part of society. It is no secret that ancient manuscripts, printed books, sources about historical figures have reached us only thanks to libraries.